Prevalence of Gestational Diabetes Mellitus in Pakistan: A Cross Sectional Study - Iram Inam, Eman Madnia, Ahmed Ammar, Saadia Sajjad, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Gestational diabetes mellitus (GDM) also known as diabetes of pregnancy is associated with adverse feto-maternal outcomes threatening the life of both mother and fetus. Timely diagnosis and early management of GDM is the key to prevent complications resulting from this incapacitating illness. Purpose of current study is to assess the prevalence of GDM in Pakistan. Methodology: A descriptive cross-sectional study was conducted. Data was collected at department of obstetrics and gynaecology from 190 pregnant women. Ethical approval was obtained from IRB of institution and informed consent was taken from all the study participants. Detailed history was gathered and oral glucose tolerance test (OGTT) performed. Data was analyzed using SPSS version 23.0. Descriptive statistics like frequencies and percentages were calculated to assess the prevalence of GDM. Results: According to age, GDM was prevalent in age group of 33-43 years 30(55%). Also educational status of participant reveals the fact that GDM was common in matric group 20(22%). Parity status >1 show more cases of GDM. Similarly, positive family history and time interval <24 months between pregnancies were prone to GDM. Out of 190, GDM was present in 18(9.47%) cases. So, in this study calculated prevalence rate was 9.47%. Study findings will help policy makers to design programs for creating public awareness regarding Gestational diabetes through the use of multiple media. Polices regarding early evaluation of gestational diabetes will help to prevent feto-maternal complications. Hence would prove fruitful to decrease the cost and burden of illness. Conclusion: It is concluded from our study that prevalence of GDM is 9.47% in Pakistan. There is a need to make early diagnosis and timely management of GDM to avoid the life threatening consequences. Policy makers should pay special attention to overcome this issue and proper antenatal visits should be planned for pregnant mothers. Keywords: Prevalence, GDM, Pregnancy, Pakistan